Zdravila za zdravljenje nevropatske bolečine - Urbanc, Marina (Farmacevtski vestnik, 2016)
There are several recommendations for the pharmacological treatment of neuropathic pain. Medicines from the first, the second and the majority of the third line of treatment can be prescribed within the scope of primary health care in Slovenia. The majority of them hold marketing authorisation with the indication for the treatment of neuropathic pain. These medicines are further described in this article.
Keywords: antidepresivi; antikonvulzivi; kapsaicin; nevropatska bolečina; opioidi